Comparing the Effect of “Ginger-Lavender Capsule” and “Mefenamic Acid” on Postpartum Pain - F Salehi; Sh Jannesari; M Nasiri; Sh Sahranavard (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Although chemical drugs are effective for postpartum pain, herbal medicines with relative safety and fewer side effects are more suitable. The aim of the present study was to compare the impact of “Ginger-Lavender” and “Mefenamic acid” capsules on postpartum pain. Methods: This triple-blind clinical trial study enrolled 94 multiparous women complaining of moderate to severe postpartum pain in Valiasr Hospital, Fasa, in 2021. They randomly divided into 2 groups (n=47): the “Ginger-Lavender” 300 mg capsules (A) and the “Mefenamic acid” 250 mg capsules (B). Measuring the pain score started 2 hours after delivery and continued every 6 hours, before and 1 hour after receiving the related drugs, until 24 hours using VAS. Findings: The demographic information of the two groups, including mothers' age and BMI, weight of newborns, breastfeeding, receiving oxytocin and the number of pregnancies and deliveries, were not significantly different. Before the intervention, there was no significant difference in pain severity between the two groups (A=5.02±1.24, B=4.72±0.97). Consuming “Ginger-Lavender” and “Mefenamic acid” capsules at different hours decreased pain severity significantly (p<0.05). No significant differences were found between the “Ginger-Lavender” and “Mefenamic acid” groups for the mean postpartum pain severity at different hours after the first (A=2.38±0.922, B=2.553±0.928), second (A=2.0217±1.242, B=2.021±1.188), third (A=1.55±0.97, B=1.61±1.07), and fourth (A=1.42±1.01, B=1.38±0.99) interventions. Conclusion: Since “Ginger-Lavender” capsules reduced postpartum pain, it is recommended to use them instead of standard drug, “Mefenamic acid” capsules, as an effective and safe herbal medicine.